Rising Income Inequality in China : A Race to the Top - Luo, Xubei; Zhu, Nong (World Bank, Washington, DC, 2012)
Income inequality in China has risen rapidly in the past decades across regions, between rural and urban sectors, and within provinces. The dynamics of divergence across these sub-national areas have taken the form of a "race to the top" - meaning that all segments of the population, including the poor with low education in lagging inland rural areas, have experienced gains in average income. The largest gains have been registered by those with higher income and education in leading coastal urban areas. Using the China Economic, Population, Nutrition and Health Survey data of 1989 and 2004, we show that the most important factors explaining overall inequality are differential returns to schooling and sector of employment. A decomposition analysis based on household income determination shows that the increase in returns to education explains two-thirds of income changes in urban areas and one-sixth in rural areas. The widening income gaps are the consequence of higher growth in leading urban and coastal areas and that the skilled population has benefited more from the economic reforms carried out during the last 25 years. The authors argue that rising income inequality can be part of a normal process of development at a certain stage, and that the dynamics of spatial income divergence in the form of "a race to the top" can be desirable to some extent as it unleashes competitive pressure and creates incentives for investment in skills. Continuing to improve market efficiency and investing in people, in particular improving education service in lagging areas to poor people, are important for sustainable growth and equitable distribution in the long run.